A distributed space-time coding in asynchronous wireless relay networks - Xiaoyong Guo, Xiaoyong Guo; Xiang-Gen Xia, Xiang-Gen Xia (IEEE transactions on wireless communications, 2008)
Jing and Hassibi recently presented a detailed analysis on the problem of distributed space-time coding for a synchronized wireless relay network, where only linear transforms are implemented at relay nodes, and proposed a linear dispersion coding scheme. In this letter, we extend it to asynchronous wireless networks by employing OFDM to combat timing errors from relay nodes. Based on a layered structure, we present a distributed space-time code design achieving full spatial diversity for an asynchronous wireless relay network.